Pulmonary Hypertension in Pregnancy: A Report of 49 Cases at Four Tertiary North American Sites. Issue 3 (March 2017) - Meng, Marie-Louise; Landau, Ruth; Viktorsdottir, Olof; Banayan, Jennifer; Grant, Tamila; Bateman, Brian; Smiley, Richard; Reitman, Elena
Abstract : OBJECTIVE: To identify whether pregnancy outcomes vary by etiology and severity of pulmonary hypertension and whether contemporary therapies influence outcomes. METHODS: A retrospective review of medical records at four academic institutions was conducted to identify pregnant women with pulmonary hypertension (2001–2015). International Classification of Diseases, 9th Revision codes for pulmonary hypertension and pregnancy were used to identify potential participants. Medical records were abstracted for demographics, management, and outcomes. Women were classified according to the 2013 World Health Organization (WHO) pulmonary hypertension classification groups 1–5. Mild pulmonary hypertension was defined as a mean pulmonary artery pressure 25–49 mm Hg and severe pulmonary hypertension as mean pulmonary artery pressure 50 mm Hg or greater or systolic pulmonary artery pressure 70 mm Hg or greater. Descriptive statistics were used to compare outcomes. RESULTS: Forty-nine women were identified. Mortality rate was 16% (n=8/49); all deaths occurred postpartum, and seven of eight deaths occurred in women with WHO group 1 pulmonary hypertension (mortality rate 23%, n=7/30). Of the women who had documented live births with known mode of delivery (n=41), mortality was 4 of 22 among women with severe pulmonary hypertension and 1 of 19 among women with mild pulmonary hypertension. Mortality among women who delivered by cesarean was 4 of 22 and was 1 of 19 among women who delivered vaginally. Neuraxial anesthesia was performed in 20 of 22 cesarean and 17 of 19 vaginal deliveries with no anesthesia-related adverse events. Women with severe pulmonary hypertension needed more advanced therapies such as inotropes, pulmonary vasodilators, and extracorporeal membrane oxygenation than did women with mild pulmonary hypertension, 19 of 26 compared with 7 of 22. Preterm delivery was more common in women with severe compared with mild pulmonary hypertension, 19 of 23 compared with 8 of 17. There was one 25-week intrauterine fetal demise, but no neonatal deaths. CONCLUSION: In this large series of pulmonary hypertension in pregnancy, mortality remained high despite advanced therapies. Maternal mortality was specific to WHO group 1 pulmonary hypertension and possibly associated with severe pulmonary hypertension. In selected patients with a favorable prognosis for vaginal birth, a trial of labor can be considered. Abstract : In women with pulmonary hypertension, maternal mortality and preterm delivery rates remain high—16% and 66%, respectively—despite the use of extracorporeal membrane oxygenation and advanced therapies.